Morfološka analiza puhastega hrasta (Quercus pubescens Willd.) v Sloveniji - Jerše, Mateja (Zbornik gozdarstva in lesarstva, 2007)
The paper presents the attempt of its authors to evaluate the morphological variability of pubescent oak (Quercus pubescens Willd.) in Slovenia. Variability is a result of adaptation of this species to the environment and possibility of hybridization with other oak species. The results of the analysis were obtained on the basis of measurements and observations of pubescent oak leaves, fruits and short shoots sampled within eight populationsin Slovenia. At each location up to five trees were selected from which up to one hundred leaves were collected from short shoots on the illuminated side of crown. On the trees with fruits, acorns were also collected. In laboratory 13 parameters of leaves, were then measured, assessedand calculated, one parameter of fruits and one parameter of short shoots. For evaluation of results descriptive, univariate and multivariate statistic methods were used. The analysis of leaf morphometry data showed significant differences between trees within populations and between populations themselves. It was also ascertained that Q. virgiliana (Ten.) Ten.could be treated within the species Q. pubescens Willd.
Keywords: listi; morfologija; plodovi; puhasti hrast; Quercus pubescens Willd.; Quercus virgiliana (Ten.); Slovenia; Slovenija